(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. It is known that there are multiple associations between physical activity and psychology for human health. One of these associations is social appearance anxiety. Social appearance anxiety is a feeling of distress associated with the perceived evaluation of one’s physical self. Some individuals feel relatively little anxiety over this perceived evaluation, while others are highly stressed. There are many studies on physical activity and anxiety, but fewer studies on the social appearance anxiety. Therefore, the aim of this research is determining social appearance anxiety of individuals interested in physical activity and examining it according to some variables. Methods. The study group of the research consisted of 38 women (age = 28.53 ± 9.1 years), 190 men (age = 26.43 ± 7.78 years) from four different fitness centres, with a total number of 228 individuals. The data were collected using Social Appearance Anxiety Scale as a data collection tool. Descriptive statistics, t test for independent groups and one-way analysis of variance (ANOVA), Tukey’s multiple comparison; Kruskal-Wallis H test in the group not normally distributed were used as statistical methods for the evaluation of data. Results. Adolescences and those aiming at losing weight demonstrated more social appearance anxiety compared to young adults and those aiming to keep fit. Conclusion. It was determined that outgoing individuals demonstrated moderate levels of social appearance anxiety towards physical activity. Social appearance anxiety of individuals did not vary according to body mass index (BMI) and gender, but it varied in dependence age group and reasons for participating in physical activity. Thus it is said that the variables of age and reasons for participating in physical activity are determinant attributes of social appearance anxiety. Keywords: exercise, fitness, anxiety.